Physical activity regulates the intestinal microbiota composition - Jurdana, Mihaela; Barlič-Maganja, Darja (Annales Kinesiologiae, 2019)
Gut microbiota is the name given today to the bacterial population living in our intestine. It provides nutrients, metabolites and affects the immune system. Recent animals and human studies suggest that regular physical activity increases the presence of beneficial microbial species of gut microbiota and improves the health status of the host. When gut bacteria diversity reduces, there are systemic consequences leading to gastrointestinal, physiological and psychological distress. This review describes the communication pathway of the microbiota-gut-brain axes and other possible mechanisms by which physical activity causes changes in microbiota composition. Furthermore, it provides the latest evidence of the beneficial role of exercise, which in turn can affect health and various disease processes. The results of research studies in this area are increasingly becoming a focus of scientific attention.